International Standards for Digital Twins - Esra Kumaş (Acta Infologica)
Interest in digital twins has grown significantly due to the maturation of enabling technologies, including cloud computing, 5G, data storage, computing capabilities, the Internet of Things (IoT), Artificial Intelligence (AI), and machine learning. As these technologies have reached a sufficient maturity level and costs have decreased, the concept of digital twins has gained prominence. Given the growing interest in digital twins, which are widely acknowledged as a fundamental component in the digitalization of production underlying smart manufacturing, the absence of standards concerning digital twin terminology, architecture, and models during application development has resulted in divergent user interpretations. This lack of standardization leads to significant confusion regarding the concept of digital twins. To alleviate this confusion, establishing guidelines and developing unified terminology and implementation procedures are crucial steps to promote the widespread adoption of digital twins. This study aims to contribute to the development of digital twins by analyzing studies that present different technologies, procedures, and standards for implementing digital twins, with a particular focus on the ISO 23247 Digital Twin Framework for Manufacturing.